Facial Expressions and Emotion Labels Are Separate Initiators of Trait Inferences From the Face - Stahelski, Anthony; Anderson, Amber; Browitt, Nicholas; Radeke, Mary (Frontiers in Psychology, 2021)
Facial inferencing research began with an inadvertent confound. The initial work by Paul Ekman and Wallace Friesen identified the six now-classic facial expressions by the emotion labels chosen by most participants: anger, disgust, fear, happiness, sadness and surprise. These labels have been used by most of the published facial inference research studies over the last fifty years. However, not all participants in these studies labeled the expressions with the same emotions. For example, that some participants labeled scowling faces as disgusted rather than angry was seen in very early research by Silvan Tomkins and Robert McCarty. Given that the same facial expressions can be paired with different emotions, our research focused on the following questions: Do participants make different personality, temperament, and social trait inferences when assigning different emotion labels to the same facial expression? And what is the stronger cause of trait inferences, the facial expressions themselves, or the emotion labels given to the expressions? Using an online survey format participants were presented with older and younger female and male smiling or scowling faces selected from a validated facial database. Participants responded to questions regarding the social traits of attractiveness, facial-maturity, honesty, and threat potential, the temperament traits of positiveness, dominance, excitability, and the Saucier Mini-marker Big Five personality trait adjective scale, while viewing each face. Participants made positive inferences to smiling faces and negative inferences to scowling faces on all dependent variables. Data from participants labeling the scowling faces as angry were compared to those who labeled the faces as disgusted. Results indicate that those labeling the scowling faces as angry perceived the faces significantly more negatively on eleven of the twelve dependent variables than those who labeled the same faces as disgusted. The inferences made by the ‘disgust’ labelers were not positive; just less negative. The results indicate that different emotion labels made to scowling faces can either intensify or reduce negativity in inferences, but the facial expressions themselves determine negativity or positivity.